1997
DOI: 10.1046/j.1365-2869.1997.00022.x
|View full text |Cite
|
Sign up to set email alerts
|

Combination of bright light and caffeine as a countermeasure for impaired alertness and performance during extended sleep deprivation

Abstract: SUMMARYEffects of four conditions (Dim Light-Placebo, Dim Light-Caffeine, Bright LightPlacebo and Bright Light-Caffeine) on alertness, and performance were studied during the night-time hours across 45.5 h of sleep deprivation. Caffeine (200 mg) was administered at 20.00 and 02.00 hours and bright-light exposure (>2000 lux) was from 20.00 to 08.00 hours each night. The three treatment conditions, compared to the Dim Light-Placebo condition, enhanced night-time performance. Further, the combined treatment of ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
72
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(80 citation statements)
references
References 3 publications
8
72
0
Order By: Relevance
“…For example, melatonin administration during the biological day decreased body temperature and reduced performance and alertness (20,27,35,45). Exposure to bright light and/or the ingestion of caffeine increased nocturnal body temperature level and improved performance when examined under controlled constant-routine conditions (5,22,50,51). While these pharmacological, physiological, and environmental stimuli are likely to affect performance via mechanisms other than body temperature (e.g., blocking of adenosine receptors by caffeine), the findings from the current study suggest that the change in body temperature that was associated with these stimuli may have contributed to the change in performance that was observed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, melatonin administration during the biological day decreased body temperature and reduced performance and alertness (20,27,35,45). Exposure to bright light and/or the ingestion of caffeine increased nocturnal body temperature level and improved performance when examined under controlled constant-routine conditions (5,22,50,51). While these pharmacological, physiological, and environmental stimuli are likely to affect performance via mechanisms other than body temperature (e.g., blocking of adenosine receptors by caffeine), the findings from the current study suggest that the change in body temperature that was associated with these stimuli may have contributed to the change in performance that was observed.…”
Section: Discussionmentioning
confidence: 99%
“…During total sleep deprivation, increased homeostatic sleep drive results in impaired performance, but when examined under constant conditions, body temperature and neurobehavioral performance levels still exhibit a circadian pattern with higher levels during the habitual waking day and lower levels during habitual sleep time at night (5). The positive relationship between rhythms in performance and body temperature has been verified by studies that have controlled for factors that can influence body temperature and performance, such as light exposure, activity, posture, nutrition, and drug intake (i.e., constant routine) (5,31,41,(49)(50)(51)(52). In studies that have manipulated body temperature via external means (e.g., altering ambient temperature, cold water immersion), it has generally been reported that cognitive function is improved by increasing body temperature slightly above the normal temperature of ϳ37°C and that cognitive function is reduced by decreasing body temperature below normal (3, 23-26, 46, 48).…”
mentioning
confidence: 95%
“…Caffeine was found to either (1) exert no effects on free recall performance in sixteen studies [7][8][9]11,[21][22][23][24][25][26][27][28][29][30][31][32]; (2) improve recall in six studies [33][34][35][36][37][38]; or (3) impair recall in three studies [8,12,39].…”
Section: Short Term Memorymentioning
confidence: 99%
“…been hypothesized that melatonin attenuates SCN-dependent mechanisms responsible for promoting and maintaining cortical and behavioral arousal at particular times in the circadian cycle (Cajochen et al, 1999a,b;Dijk and Czeisler 1995;Sack et al, 1997;Wright, 1997).…”
Section: Do Light Effects Impact On Sleep and Wakefulness Irrespectivmentioning
confidence: 99%